2002
DOI: 10.1034/j.1399-5618.2002.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping and its correlates among caregivers of patients with bipolar disorder: a preliminary study

Abstract: Appraisal by, and burden on caregivers play a major role in determining their style of coping. These factors largely accounted for the differences in coping observed between caregivers of patients of bipolar disorder and schizophrenia, in this study. Reducing burden on caregivers and enhancing their awareness of illness could lead to adoption of more adaptive coping styles by them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
3
15

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 23 publications
13
110
3
15
Order By: Relevance
“…In our study we found quality of life to be moderately low in the caregivers. This is similar to the findings by Allison M. R. Lee et al [12], Perlick DA et al [13], , M. Reinares et al [14], Ogilvie AD et al [15], Heru AM et al [16], S.Chakrabarti et al [6], D Perlick et al [17] who have reported moderate to high levels of burden among caregivers of Bipolar patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study we found quality of life to be moderately low in the caregivers. This is similar to the findings by Allison M. R. Lee et al [12], Perlick DA et al [13], , M. Reinares et al [14], Ogilvie AD et al [15], Heru AM et al [16], S.Chakrabarti et al [6], D Perlick et al [17] who have reported moderate to high levels of burden among caregivers of Bipolar patients.…”
Section: Discussionsupporting
confidence: 89%
“…But very few studies from India have been done on the quality of life of caregivers of bipolar mood disorder patients [4], [5], [6], [7], [8]. Considering the increasing interest in the quality of life of caregivers of patients of bipolar mood disorder all over the world, we thought that this study will be fruitful in understanding quality of life of such caregivers in our cultural setup.…”
Section: Introductionmentioning
confidence: 99%
“…Results can only be discussed when adequately combined with findings from other studies, because theoretical assumptions of the stress process are, as a rule, very complex. In our study design, we focused on appraisal processes and person variables, whereas the representation of coping-the importance of which for PD has already been demonstrated by many authors (e.g., Pearlin et al 1990;Magliano et al 1995 andChakrabarti and Gill 2002)-was limited. Because the mean duration of one interview lasted between 2 1/2 and 3 h, a classic questionnaire such as COPE (Carver et al 1989) could not be used.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Este aumento del uso de estas tres estrategias de afrontamiento consideradas adaptativas es coherente con el modelo de competencias de Costa y López (2006). Las estrategias de Solución de problemas y de Restructuración cognitiva constituyen esfuerzos constructivos por modificar o lograr un mejor ajuste y manejo de las situaciones problemáticas o difíciles, las cuales aparecen en la literatura como las más relacionadas con una disminución del malestar psicológico del cuidador (Chakrabarti y Gill, 2002;Chandrasekaran, Sivaprakash y Jayestri, 2002;Gerson et al, 2011;Magliano et al, 2000). Estas estrategias tienen un gran valor en la medida que son estrategias orientadas a resolver los problemas.…”
Section: Discussionunclassified